SYSTEM IDENTIFICATION - Thakur, Adwait; Sankhe, Aditya (International Journal of Students’ Research in Technology & Management, 2015)
The basic objective is to construct a Transfer function of the given system. Closed loop system identification and validation are important components in dynamic system modeling. In this report a comprehensive literature survey is compiled on System Identification with a specific focus on closed loop system identification and issues of identification experiment design and model validation. This is followed by simulated experiment on a known Non-Linear system. The identified model structure can be compared with various mathematical models like ARX model, ARMAX model & OE model.